Effect of head accelerations on dynamic balance in collegiate women`s rugby - Schussler, E.; McCann, R. S.; Reilly, N.; Campbell, T. R.; Martinez, J. C. (International Journal of Athletic Therapy & Training, 2021)
The effect of subconcussive impacts on balance are not well known. The purpose of this study is to determine the effect of subconcussive impacts on dynamic balance over the course of a rugby season. Significant negative linear correlations were found between total peak linear acceleration and dominant leg (r = -.585, p = .046) and bilateral score (r = -.615, p = .033); also between total impacts over 10g and dominant leg (r = -.653, p = .021), nondominant leg (r = -.687, p = .014), and the combined total (r = -.731, p = .007). Results indicate subconcussive impacts may affect dynamic balance over the course of a competitive season of women`s collegiate rugby.